2018
DOI: 10.1111/jcmm.14000
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral sympathetic stellate ganglionectomy attenuates myocardial remodelling and fibrosis in a rat model of chronic volume overload

Abstract: Reducing sympathetic neurohormone expression is a key therapeutic option in attenuating cardiac remodelling. Present study tested the feasibility of attenuating cardiac remodelling through reducing sympathetic neurohormone level by partial cardiac sympathetic denervation in a rat model of chronic volume overload. Male Sprague‐Dawley rats were randomized into sham group (S, n = 7), aortocaval fistula group (AV, n = 7), and aortocaval fistula with bilateral sympathetic stellate ganglionectomy group (AD, n = 8). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…TGF-β1 signaling was also activated in this model. (2) The above changes could be partly reversed by bilateral SGX, suggesting that the previously observed beneficial effects of bilateral SGX in this model (Zhang et al, 2019) were at least partly mediated by downregulating TGF-β1 signaling. (3) In vitro results further evidenced the positive causal relationship among NE, TGF-β1, and myocardial fibroblast proliferation.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…TGF-β1 signaling was also activated in this model. (2) The above changes could be partly reversed by bilateral SGX, suggesting that the previously observed beneficial effects of bilateral SGX in this model (Zhang et al, 2019) were at least partly mediated by downregulating TGF-β1 signaling. (3) In vitro results further evidenced the positive causal relationship among NE, TGF-β1, and myocardial fibroblast proliferation.…”
Section: Discussionmentioning
confidence: 71%
“…We previously showed that bilateral SGX attenuated cardiac remodeling and fibrosis under chronic volume overload. Our previous results showed that the weights of the left and right ventricles and the heartto-body ratio were increased under chronic volume overload, which were decreased by bilateral stellate ganglionectomy (Zhang et al, 2019). The collagen of heart tissue sections was detected by Sirius red staining.…”
Section: Effect Of Bilateral Sgx On Cardiac Ecm Remodeling-related Signaling Under Chronic Volume Overloadmentioning
confidence: 97%
See 3 more Smart Citations